PENGARUH KESADARAN WAJIB PAJAK, PEMAHAMAN PSAK EMKM DAN RELAKSASI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PELAKU USAHA MIKRO KECIL MENENGAH DI KOTA YOGYAKARTA - Rofina Ernesta Habu; Sri Ayem; Dewi Kusuma (Universitas Muhammadiyah Makassar, 2021)
This study aims to test whether taxpayer awareness, understanding of Understanding Financial Accounting Standards of Small and Medium Micro Eentitas and tax relaxation to the compliance of small and medium micro enterprises taxpayers. The population in this study is Small and Medium Micro Enterprises in Yogyakarta. Sampling techniques in this study use convenience sampling. Data collection is done by disseminating questionnaires in the form of google form through whatsap application to respondents. The number of questionnaires processed as many as 62 questionnaires, from google form. The data was analyzed using multiple linear regression analysis. The results of this study show that taxpayer awareness and tax relaxation have a positive and significant effect on taxpayer compliance. Meanwhile, understanding the Understanding of Financial Accounting Standards of Small and Medium Micro Eentitas negatively affects taxpayer compliance.